Changes in B Cell Pool of Patients With Multibacillary Leprosy: Diminished Memory B Cell and Enhanced Mature B in Peripheral Blood - Nogueira, Otto Castro; Gandini, Mariana; Cabral, Natasha; de Figueiredo, Vilma; Rodrigues-da-Silva, Rodrigo Nunes; Lima-Junior, Josué da Costa; Pinheiro, Roberta Olmo; Pereira, Geraldo Moura Batista; Pessolani, Maria Cristina Vidal; de Macedo, Cristiana Santos (Frontiers in Immunology, 2021)
Despite being treatable, leprosy still represents a major public health problem, and many mechanisms that drive leprosy immunopathogenesis still need to be elucidated. B cells play important roles in immune defense, being classified in different subgroups that present distinct roles in the immune response. Here, the profile of B cell subpopulations in peripheral blood of patients with paucibacillary (TT/BT), multibacillary (LL/BL) and erythema nodosum leprosum was analyzed. B cell subpopulations (memory, transition, plasmablasts, and mature B cells) and levels of IgG were analyzed by flow cytometry and ELISA, respectively. It was observed that Mycobacterium leprae infection can alter the proportions of B cell subpopulations (increase of mature and decrease of memory B cells) in patients affected by leprosy. This modulation is associated with an increase in total IgG and the patient's clinical condition. Circulating B cells may be acting in the modulation of the immune response in patients with various forms of leprosy, which may reflect the patient's ability to respond to M. leprae.